Determinants of Islamic Consumption Behavior: A Study of Gen Z in Surabaya - Sania Ardiana; Rachma Indrarini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Technological and internet developments in the economic field have had an impact on buying and selling activities. Currently, consumption activities can be carried out anywhere in real time through live streaming. The purpose of this study is to analyze the influence of live streaming, lifestyle, religiosity, and income on the consumption behavior of Generation Z Muslims in the city of Surabaya. The research method used is quantitative with primary data sources obtained through the distribution of online questionnaires. Sampling was conducted using purposive sampling with 241 respondents. Data analysis techniques used structural equation modeling-partial least squares (SEM-PLS) on SmartPLS 4.1 software. The data analysis model used an outer model, inner model, model fit evaluation, and hypothesis testing. The results showed that there was a significant positive influence of live streaming, religiosity, and income on Islamic consumption behavior, while lifestyle did not have a significant positive influence on Islamic consumption behavior. This indicates that the rise of live streaming shopping does not cause Generation Z to shop solely based on desire and that they continue to practice Islamic consumption behavior.